Prevalence and trajectories of subjective cognitive complaints and implications for patient outcomes: a prospective study of haemodialysis patients - Chan, Frederick H. F. (2023)
Cognitive impairment is common in haemodialysis patients and is associated with increased hospitalization and mortality. However, subjective cognitive complaints (SCCs), the self-experienced difficulties in everyday cognitive activities, remain poorly understood. This study examined the prevalence and course of SCCs in haemodialysis patients and its longitudinal associations with sociodemographic, clinical and patient-reported variables.